A nudity-based intervention to improve body image, self-esteem, and life satisfaction. (22nd October 2020) - West, Keon
An individual's body image has profound implications for their self-esteem and overall life-satisfaction, and is a significant predictor of the onset of eating disorders. Recent research suggested that nude activities improved body image, self-esteem, and life-satisfaction among participants who were predisposed to take part in such activities. This current research investigated whether a nudity-based intervention can have similar positive effects among non-nudist participants with low levels of positive body-image, and whether those effects endure. Fifteen participants completed measures of body-image, self-esteem, and life-satisfaction before, immediately after, and one month after participating in a 4-day, nudity-based intervention. Participants reported substantial improvements in all three outcomes that remained one month after the intervention's completion. Results suggest that nudity-based interventions can meaningfully and enduringly improve body image and related outcomes, even among non-nudists.